Tourism and hospitality marketing - Arenas, Chester Dave G. (Manila : Edric Publishing House, 2021)
This book presents a variety of practical application tools, skills, practices, models, approaches and strategies that are proving themselves effective in tourism marketing.
CHAPTER 1. An overview of marketing in the Hospitality industry -- 2. Marketing environment and SWOT Analysis -- 3. The marketing strategy & role of marketing in hospitality industry -- 4. The marketing management process -- 5. Product mix -- 6. Price mix -- 7. Place Mix -- 8. Promotions Mix.
Includes bibliographical references.
Keywords: TOURISM -- MARKETING; HOSPITALITY INDUSTRY -- MARKETING